2013
DOI: 10.1123/tsp.27.3.258
|View full text |Cite
|
Sign up to set email alerts
|

NCAA Division I Coaches’ Perceptions and Preferred Use of Sport Psychology Services: A Qualitative Perspective

Abstract: Although there appears to be greater acceptance and use of sport psychology (SP), fully integrating SP consultants and services into college athletic programs has yet to occur in most institutions. Decisions to initiate, continue, or terminate SP services are often made by coaches. Therefore, college coaches with access to services were interviewed to explore their beliefs and expectations about SP service use and how an SP consultant could work effectively with them and their athletes. Using consensual qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 32 publications
0
37
0
Order By: Relevance
“…The best way to achieve this collaborative approach between services, professionals, and community groups is to coordinate regular multidisciplinary team meetings to discuss and evaluate the progress of individual athletes. When coordinating these multidisciplinary teams, each campus must decide which professionals, services, and organizations should be included within this network of collaborative care, identify their framework for collaboration, and then determine how the university's infrastructure will synchronize efforts to serve student-athletes (Hayden, Kornspan, Bruback, Parent, & Rodgers, 2013;Zakrajsek, Steinfeldt, Bodey, Martin, & Zizzi, 2013).…”
Section: Campus Community Levelmentioning
confidence: 99%
“…The best way to achieve this collaborative approach between services, professionals, and community groups is to coordinate regular multidisciplinary team meetings to discuss and evaluate the progress of individual athletes. When coordinating these multidisciplinary teams, each campus must decide which professionals, services, and organizations should be included within this network of collaborative care, identify their framework for collaboration, and then determine how the university's infrastructure will synchronize efforts to serve student-athletes (Hayden, Kornspan, Bruback, Parent, & Rodgers, 2013;Zakrajsek, Steinfeldt, Bodey, Martin, & Zizzi, 2013).…”
Section: Campus Community Levelmentioning
confidence: 99%
“…Therefore, it is important to examine the attitudes coaches hold towards sport psychology consultants and the services they can provide. There are a number of studies that have examined attitudes towards sport psychology by coaches in different contexts, including youth sport coaches , high school coaches (Zakrajsek et al, 2011), collegiate coaches (Allen, 2013;Zakrajsek et al, 2013), and Olympic coaches (Gould et al, 1991). conducted a review of the literature on attitudes towards sport psychology and seeking sport psychology services.…”
Section: Attitudes Towards Sport Psychologymentioning
confidence: 99%
“…There is also a paucity of research examining the motivation and attitudes of coaches for utilizing a sport psychology consultant (SPC). Factors that have been identified to positively influence a coach's attitude towards utilization of a SPC with their athletes include coach demographic factors (i.e., older age, more years of coaching experience, higher level of education ;Zakrajsek, et al, 2011;and being female;, and the abilities of SPCs themselves (i.e., ability to build a trusting relationship, fit in with the team, maintain professional boundaries, and work within the coach's own system; Zakrajsek, et al, 2013). also indicated that the most consistent and influential factor contributing to confidence in using SPCs is a coach's previous knowledge and experience with sport psychology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, researchers examining mental training suggest that college coaches believe that mental skills are important to the success of their respective teams and have an interest in sport psychology services being available to their teams (Zakrajsek, Steinfeldt, Bodey, Martin, & Zizzi, 2013). Despite the indicated importance of mental skills and the value of having sport psychology services available, usage rates of sport psychology services across all three NCAA divisions hover between 20% and 30% (Wrisberg, Loberg, Simpson, Withycombe, & Reed, 2010).…”
Section: Ncaa Coaches' Perceptions Of Sport Psychology Servicesmentioning
confidence: 99%